REVIEW OF THE TAXONOMY, ETHNOBOTANY, PHYTOCHEMISTRY, PHYTOTHERAPY AND PHYTOTOXICITY OF GERMANDER PLANT (TEUCRIUM POLIUM L.) - Jaradat, Nidal AMIN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Medicinal plants and phytogenic products have used for treatment of various diseases from ancient times in the folklore medicine all over the world. Crude plants extracts are now considered a valuable source for natural products used in the development of medicines against various diseases, for the development of pharmaceutical preparations, and for novel biomedical researches. Germander (Teucrium polium L.) is a shrubby plant widely distributed in the mountains, hills and deserts of the Mediterranean regions and considered one of the most useful traditional medicinal plants in Palestine and other Middle Eastern countries. It has been used for centuries in the ethnopharmacology for the treatments of many pathophysiological conditions, such as diabetes, gastrointestinal disorders, rheumatism, inflammations, also used as diuretic, antipyretic, tonic, diaphoretic, analgesic, antihyperlipidemic and other disorders. During the last five decades, apart from the phytochemical characterization of the components of the T. polium plant, there has been significant interest in the medicinal applications and biological activity of this plant. This review summarizes more than 50 years of scientific knowledge of Germander. It provides an overview on its taxonomy, biological activities, the most well-known isolated compounds from all the plants parts, clinical studies, and pharmacological activities. Evidence-based medicinal applications of the plant extracts have been discussed along with their safety evaluation, especially the recent evidence for hepatotoxicity secondary to the long term use of this plant. Keywords: Teucrium polium L, Biological activity, Ethnobotany, Phytochemical constituents, Phytotherapy, Phytotoxocity.